Uma História de Violência sob as Brumas des Virunga. Morte e poder no Ruanda - Fernando Florêncio (Cadernos de Estudos Africanos)
This article presents a personal view to understand the historical relationship of the two main ethnic groups in Rwanda, the Bahutu and the Batutsi. Since the independence of Rwanda, in 1961, these two ethnic groups are involved in a constant cycle of violence for the hegemonic control of the State and the domination of one against the other. We aim to show also that the political fight in Rwanda broke up the civil war in Zaire and the outcoming of the Democratic Republic of Congo.